The Impact of Internet-Based Corporate Governance Sharia (IBCGS) Rating on Shareholders Trust in Jakarta Islamic Index Companies - Ulil Hartono; Musdholifah Musdholifah; Ika Diyah Candra Arifah; Riska Dhenabayu; Trias Madanika Kusumaningrum (Universitas Negeri Surabaya, 2021)
The purpose of this research is to present the quality measurement of internet-based Islamic corporate governance and identify its effects on stakeholder trust. In measuring the implementation of corporate governance, this study uses the method of measuring the quality of Islamic corporate governance (IBCGS), as the development of IBCG and IBCG Rating Modified. This research uses descriptive exploratory analysis tools with PLS-SEM as the statistical tool. The object of this research is a company registered in the Jakarta Islamic Index (JII). The results showed that the implementation of corporate governance based on IBCGS by sample companies had been implemented but with varying quality. Meanwhile, the implementation of corporate governance in sharia companies positively influences shareholder trust manifested by their return on equity, stock returns and earnings per share. The findings of this study are expected to contribute to the signalling theory and agency theory in explaining the influence of the quality of corporate governance on the shareholder trust that should be concerned by sharia companies.